Prinsip Akuntabilitas dalam Etika Profesi Menteri Pada Polemik Viral Tagar #KaburAjaDulu - Diajeng Dhea Annisa Aura Islami; Diah Ayu Wulandari; Adelia Yuliana; Aura Anisah; Rena Putri Nirwana; Juanita Alifia Adilla; Salma Elsa Anindya; Mulyadi Mulyadi (Jurnal Litigasi Amsir, 2025)
Officials have an important role in government, so in taking action and responding to an event or case that occurs, the accountability of state officials must be oriented toward the interests of citizens. With the rise of the #KaburAjaDulu trend, state officials are held accountable for every policy and statement issued. Based on the controversial statement issued by the deputy minister of labour, which is explained in Pasal 58 huruf j Undang-Undang Nomor 20 Tahun 2023 concerning the State Civil Apparatus, it states that ministers and ministerial-level positions are state officials. So if a public official issues a statement that tends to ignore or underestimate public unrest, this can be categorised as an ethical violation because it does not follow the principles of responsible leadership and is oriented toward the public interest. With this, it can be seen how the principle of accountability is regulated in the professional ethics of a minister according to legal norms and the Code of Ethics for State Officials and how the application of the principle of accountability by a minister in dealing with the viral polemics of the #KaburAjaDulu hashtag. So that it can find out the performance of state officials and provide ethics and professionalism training to realize a better, more efficient, and accountable government